Allopurinol Loaded Transferosomes for the Alleviation of Symptomatic After-effects of Gout: An Account of Pharmaceutical Implications - Tiwari, Ruchi; Tiwari, Gaurav; Singh, Rachna (Current Drug Therapy, 2020)
Background: The present study assessed the transdermal potential of transferosomes loaded with allopurinol for the treatment of gout. Methods: Transferosomes of allopurinol were composed of different ratios of tween-80, soya lecithin and solvent using a thin-film hydration method. Transferosomes were characterized for Scanning Electron Microscopy (SEM), zeta potential, % entrapment efficiency (%EE), Fourier Transform Infrared Spectroscopy (FTIR), in-vitro drug release and kinetics as well as stability. Then, optimized formulation was incorporated in gel and evaluated for viscosity, pH, extrudability, homogeneity, skin irritation study, spreadability, ex vivo skin permeation study, flux, and stability. Results: SEM studies suggested that vesicles were spherical and zeta potential were in the range of -11.4 mV to -29.6 mV and %EE was 52.4- 83.87%. FTIR study revealed that there was no interaction between allopurinol and excipients during the preparation of transferosomes. The cumulative percentage of drug release from various transferosomes was ranged from 51.87 to 81.87%. A transferosomal gel of F8 formulation was prepared using dispersion method reported pseudoplastic rheological behavior, optimum pH, spreadability and maximum drug permeation i.e. 79.84% with flux 13.06 g/cm2/hr, followed zero-order release kinetics. Irritation and in-vivo studies of optimized transferosomal gel G8 on rabbits revealed better results than the standard allopurinol. Conclusion: This research suggested that allopurinol loaded transferosomal gel can be potentially used as a transdermal drug delivery system for the treatment of gout.
Keywords: transferosomal gel